A guide to the field guides to the herpetofauna of Borneo - Indraneil, Das; Aaron M., Bauer (Society for the Study of Amphibians and Reptiles, 2024)
To facilitate interest in Bornean herpetofauna, we review current herpetological literature and list resources for identification of the island’s herpetofauna, including in-print books and websites.